Faith in nation exclusionary origins of nationalism - Marx, Anthony W. (New York : Oxford University Press, 2003)
"In a startling departure from a historical consensus that has dominated views of nationalism for the past quarter century, Marx argues that European nationalism emerged ... in the early modern era, as a form of mass political engagement based on religious conflict, intolerance, and exclusion. Challenging the self-congratulatory genealogy of civic Western nationalism, Marx shows how state-builders attempted to create a sense of national solidarity to support their burgeoning authority. Key to this process was the transfer of power from local to central rulers; the most suitable vehicle for effecting this transfer was religion and fanatical passions."
1. History and Arguments -- 2. Amassing State and Gathering Storm -- 3. Founding Exclusions -- 4. Interregnums of Coexistence and State-Building -- 5. Cohesion by Exclusion, Redux from Above -- 6. Superimposing Democratic Inclusion on Forgotten Exclusions -- 7. Angel of History and Patron Saint of Nationalism.
Includes bibliographical references (p. 239-249) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nationalism -- Philosophy; Europe -- Religion; Electronic books